PERAN DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN DALAM PENANGANAN SAMPAH DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR TAHUN 2022-2023 - Dermawan, Andre; Nasution, Hazqon Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Waste management is a mandatory government responsibility, although not included in basic services, particularly in the environmental sector. The government's role in waste management is crucial to creating a clean, tidy, and healthy environment, and preventing the spread of waste without proper management. Difficulties in managing waste effectively are caused by the unequal availability of waste management facilities, government policies and regulations, including sanctions for violators, low public awareness of proper waste disposal, and other factors such as socioeconomic conditions that influence waste management culture and behavior. This research was conducted in Tembilahan District, Indragiri Hilir Regency with the aim of describing the government's role in waste management. The method used is a qualitative approach with a qualitative descriptive research type. The theoretical basis uses the role theory of Ryaas Rasyid which includes three main indicators, namely: 1) Regulator, 2) Dynamicator, and 3) Facilitator. Based on the research results and referring to Ryaas Rasyid's theory (in Labolo, 2010), in the regulator indicator, the government has issued regional regulations; however, implementation in terms of law enforcement and imposing sanctions on violators is still not optimal. From the Dynamic indicator of the government's role, the relevant agency has formulated public service innovations, namely the Waste Patrol Team (TIMPAS) and the Environmental Complaint System (SI PANGLINK) to help educate the public through socialization and is running well. In the facilitator indicator, the government's role in providing waste management facilities and infrastructure has not been evenly understood. The conclusion that the government's role is still less than optimal is evident in the regulator and facilitator indicators, and the dynamic indicator that is already in place through public service innovation programs. Keywords: Government Role, Environment, Waste Management.